2019
DOI: 10.5194/acp-19-14901-2019
|View full text |Cite
|
Sign up to set email alerts
|

A study of volatility by composition, heating, and dilution measurements of secondary organic aerosol from 1,3,5-trimethylbenzene

Abstract: Abstract. Studies of the volatility distribution of secondary organic aerosol (SOA) from aromatic compounds are limited compared with SOA from biogenic monoterpenes. In this study, the volatility distribution was investigated by composition, heating, and dilution measurements for SOA formed from the photooxidation of 1,3,5-trimethylbenzene in the presence of NOx. Composition studies revealed that highly oxygenated monomers (C9H14Ox, x = 4–7) and dimers (C18H26Ox, x = 8–12) are the major products in SOA particl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 49 publications
3
46
0
Order By: Relevance
“…As the concentration of 1,3,5-TMB is much higher than that of n-dodecane in both the gasoline compositions and ambient air, the initial concentration ratio of 1,3,5-TMB and n-dodecane in this work is about 10 : 1 (ppbv). Schauer et al (2002) reported that 1,3,5-TMB and n-dodecane in the gasoline composition were about 7450 and 136 µg g −1 , respectively; Gentner et al (2012) reported that the weight percentages of 1,3,5-TMB and n-dodecane in liquid gasoline were 0.530-0.881 and 0.004-0.045 (% weight by carbon), respectively. According to field observations in China, the measured 1,3,5-TMB concentration at the rural site in the YelRD (Yellow River Delta) region in 2017 could reach 1.447 ppb , and the measured C 12 alkane concentration was 0.122 ± 0.12 ppb in the PRD (Pearl River Delta) region and 0.129 ± 0.086 ppb in the NCP (North China Plain) region in 2018 (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As the concentration of 1,3,5-TMB is much higher than that of n-dodecane in both the gasoline compositions and ambient air, the initial concentration ratio of 1,3,5-TMB and n-dodecane in this work is about 10 : 1 (ppbv). Schauer et al (2002) reported that 1,3,5-TMB and n-dodecane in the gasoline composition were about 7450 and 136 µg g −1 , respectively; Gentner et al (2012) reported that the weight percentages of 1,3,5-TMB and n-dodecane in liquid gasoline were 0.530-0.881 and 0.004-0.045 (% weight by carbon), respectively. According to field observations in China, the measured 1,3,5-TMB concentration at the rural site in the YelRD (Yellow River Delta) region in 2017 could reach 1.447 ppb , and the measured C 12 alkane concentration was 0.122 ± 0.12 ppb in the PRD (Pearl River Delta) region and 0.129 ± 0.086 ppb in the NCP (North China Plain) region in 2018 (Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our observations show good agreement with ion formulas observed in these experiments, with divergence at significantly higher NOx conditions (Hammes et al, 2019). This includes observations of ions such as C9H12O(2-8) (Molteni et al, 2018) alongside ions observed by LC-ToF-MS (Sato et al, 2012(Sato et al, , 2019 which were all important in our experiments (Table S1). Ring retention was previously found to 500 contribute ~ 25 % of SOA mass from a study 1,2,4-trimethyl benzene under elevated NOx conditions which were attributed to BPR, phenolic and benzaldehyde channels despite low ring-retaining concentrations in the gas phase, consistent with our observations.…”
Section: Ring-retaining Productsmentioning
confidence: 84%
“…In this study we investigate a range of isomers of C9-aromatics to evaluate this effect in more detail. Of the aromatics studied in these experiments, molecular understanding of SOA products is most well developed for the trimethyl benzene isomers (Huang et al, 2014;Li and Wang, 2014;Sato et al, 2012Sato et al, , 2019. Though other aromatics have been studied, these have either lacked molecular level detail or focused on gas phase oxidation and lacked detailed characterisation of SOA (Chan et al, 2009;Li et al, 2016;Molteni et al, 2018;Ping, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The representative identified products with strong intensity are shown in Figure S2 and Table 2. The identified products are mainly based on the mass spectra and previous related studies (Tsiligiannis et al, 2019;Li et al, 2017a;Sato et al, 2019). Huang et al (2015) reported that the predominant products for aging of 1,3,5-trimethylbenzene secondary organic aerosol were organic nitrogen-containing products, aromatic organic acid, oxocarboxylic acid, and oligomer compounds.…”
Section: Enhancement Of Soa Formationmentioning
confidence: 99%